Comparing cracking time and structure changes of different high‐density polyethylenes during stress and photo‐oxidative aging. Issue 20 (15th May 2014) - Huang, Zhengyu; Li, Yongliang; Ren, Xiancheng
ABSTRACT This article describes the structure changes of high‐density polyethylene (HDPE) during stress and photo‐oxidative aging experiments, and the relationship between different materials and cracking time. The three most representative grades of HDPE are 9070, TR480, and 2480NT. The average molecular weight, the comonomer type, and content of materials were measured by high‐temperature gel permeation chromatography, 13C nuclear magnetic resonance (NMR) spectroscopy, and successive self‐nucleation and annealing technique. Moreover, tensile testing was done to distinguish different toughness of materials. The samples were exposed to 5 MPa stress and ultraviolet irradiation in an aging oven, and observed at time intervals. The changes in structure were characterized by metallurgical microscopy, differential scanning calorimetry, attenuated total reflection‐Fourier transform infrared spectroscopy, X‐ray diffraction, and gel content measurements. With increasing time, the crystallinity increased, whereas melting point and oxygen induction times decreased. Meanwhile, the carbonyl index values and gel content reached about 10% until the samples were cracked. The results manifested that the resistance to cracking of the different HDPEs followed the order: 2480NT > TR480 > 9070. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40904.